Application of stable isotope analysis to differentiate shrimp extracted by industrial fishing or produced through aquaculture practices - Gamboa Delgado, Julián; Molina Poveda, César; Godínez Siordia, Daniel Enrique; Villarreal Cavazos, David Alonso; Ricque Marie, Denis; Cruz Suárez, Lucía Elizabeth (National Research Council Canada, 2014)
Carbon and nitrogen stable isotope values were determined in Pacific white shrimp (Litopenaeus vannamei) with the objective of discriminating animals produced through aquaculture practices from those extracted from the wild. Farmed animals were collected at semi-intensive shrimp farms in Mexico and Ecuador. Fisheries-derived shrimps were caught in different fishing areas representing two estuarine systems and four open sea locations in Mexico and Ecuador. Carbon and nitrogen stable isotope values (δ13CVPDB and δ15NAIR) allowed clear differentiation of wild from farmed animals. δ13CVPDB and δ15NAIR values in shrimps collected in the open sea were isotopically enriched (−16.99‰ and 11.57‰), indicating that these organisms belong to higher trophic levels than farmed animals. δ13CVPDB and δ15NAIR values of farmed animals (−19.72‰ and 7.85‰, respectively) partially overlapped with values measured in animals collected in estuaries (−18.46‰ and 5.38‰, respectively). Canonical discriminant analysis showed that when used separately and in conjunction, δ13CVPDB and δ15NAIR values were powerful discriminatory variables and demonstrate the viability of isotopic evaluations to distinguish wild-caught shrimps from aquaculture shrimps. Methodological improvements will define a verification tool to support shrimp traceability protocols.